Analysis of Financial Variables on Conventional BPR Performance - Ferdinansyah Ferdinansyah; Hidayat Sofyan Wijaya; Selamet Riyadi (Ridwan Institute, 2023)
This study aims to analyze the financial ratios of rural banks registered with Bank Indonesia to banking performance. The number of samples used was 10 Conventional Rural Banks located in Java and Sumatra and registered with Bank Indonesia, with a research period between 2010 to 2014. The analysis method used is regression analysis with panel data using an e-views program. The results showed that together the independent variables used in this study had a significant influence on BPR performance while individually the ROA, LDR and NIM variables did not have a significant influence on BPR performance. NPL variables have a positive and significant influence on BPR performance. BOPO variables have a negative and significant influence on BPR performance. The independent variables in this study were able to influence the dependent variable by 60.30%. This shows that together the variables NPL, ROA, BOPO, LDR and NIM are able to affect BPR performance by 60.30%.